A Practice-Based Governance Framework for Managing Digital and Sustainable Transformation - Foit, Dörte; Scholz, Thorben; Silke Schlege, Anna Marie (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The dual transformation towards sustainability and digitalization confronts manufacturing companies with complex and often conflicting governance demands. Although governance is increasingly seen as a key enabler of organizational change, existing approaches rarely address the integrated challenges of simultaneous sustainability and digital transformation. We present a practice-based Dual Governance Framework that supports organizations in strategically embedding and operationalizing dual transformation. Developed through iterative design science research, the framework builds on academic literature, stakeholder input from a multi-partner research consortium, and insights from industry pilot projects. It identifies six governance areas, including integrated business strategy and compliance, and links them to six overarching principles such as stakeholder integration and transparency. To facilitate operationalization, we introduce the Dual Governance Map that enables structured reflection across governance domains and supports context-specific development. The framework provides a coherent and actionable governance architecture that bridges theory and practice and supports dialogue with internal and external stakeholders.